2021
DOI: 10.1155/2021/9916050
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Mortality among Cervical Cancer Patients Attending in Tikur Anbessa Specialized Hospital, Ethiopia: Institutional-Based Retrospective Study

Abstract: Background. Globally, about 570,000 cases and 311,000 deaths of cervical cancer occurred in 2018. It was the leading cause of cancer-related deaths among women in Africa. The global mean age at death of cervical cancer was about 59 years. This study aimed to assess the determinants of cervical cancer mortality among cervical cancer patients attending in Tikur Anbessa Specialized Hospital (TASH). Methods. Institutional-based retrospective cohort study was conducted in the oncology center of TASH, Ethiopia, from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 36 publications
2
7
0
Order By: Relevance
“…The mortality rate in this study is substantial, but very strongly correlated with the recent estimate of 31 per 100-women years in Ethiopia ( 9 ). However, it also varies widely from estimates in other previous studies with the rates ranging from 15.6 to as high as 79.8 per 100 women-years ( 10 , 11 ). This may be due to the selection of the study population as mortality from hospital-based data are usually higher than that of the population.…”
Section: Discussionmentioning
confidence: 63%
See 3 more Smart Citations
“…The mortality rate in this study is substantial, but very strongly correlated with the recent estimate of 31 per 100-women years in Ethiopia ( 9 ). However, it also varies widely from estimates in other previous studies with the rates ranging from 15.6 to as high as 79.8 per 100 women-years ( 10 , 11 ). This may be due to the selection of the study population as mortality from hospital-based data are usually higher than that of the population.…”
Section: Discussionmentioning
confidence: 63%
“…Our study shows that anemia significantly reduces disease-specific survival by more than 80%. A possible mechanism responsible for this is anemia-induced hypoxia which is associated with decreased tumor susceptibility to anticancer medications and increased morbidity in general ( 10 , 44 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of 11 studies considered other measures of cervical cancer burden; five studies reported mortality globally including Africa ( 117 , 144 ), South Africa ( 129 ), Kenya ( 139 ) and Ethiopia ( 97 ). One cross-sectional study reported the population attributable fraction in a GLOBOCAN study ( 108 ) Two cross-sectional studies reported the disability-adjusted life years (DALYs) in Kenya ( 115 ) and for the SSA region ( 119 ).…”
Section: Resultsmentioning
confidence: 99%